Parenting of Children with Special Needs for Parents and Teachers, as Well as Supporting Educational Media to Improve the Quality of Education at Muhammadiyah SLB Kutoarjo - Yoni Astuti; Nurul Aisyah; Nisa Kartika Hasanah (Universitas Muhammadiyah Yogyakarta, 2022)
Aspects of child development occur sequentially starting from the womb, babies, to children. If a child misses one stage of development that should be followed, it will affect another stage of development. Students at the Muhammadiyah Kutoarjo Special School (SLB) have various developmental barriers including deafness, mental retardation, autism, physical disability, so they require different treatment. Therefore, teachers and parents need knowledge to understand the development and obstacles of these children so that they are appropriate in helping the growth and development of SLB children. The purpose of this service is to improve the care and education of extraordinary children, and to provide educational tools to improve aspects of the development of special school children. The method given is in the form of lectures and discussions. The results of service, to overcome child development barriers on the orders of educational therapy tools such as footbridge and sandbox, gym ball, clay, water bath. there is an increase in activities, namely Titian and Sandbox and Gym Balls which are used on Thursdays during the exercise schedule. Clay is used on Wednesday while skill schedule and waterbeads are used on Tuesday. The order of the tourist materials of interest is 100% gym ball, while for the footbridge and sandbox, clay, water bath in the order; 95.7; % 82.6%; 60.8%. Conclusion This activity went smoothly and according to the planned schedule. There is an increase in children's activities 3 times a week. The gym ball is the most popular medium for children.